One rainy day - Butler, M. Christina; Macnaughton, Tina (London : Little Tiger Press, 2008)
When Little Hedgehog goes for a walk one rainy day, his new umbrella proves its value in most unexpected ways.
"A shiny, Touch-and-feel book"--Cover.
2.9
K-3.
K-3
Keywords: Animals -- Juvenile fiction; Hedgehogs -- Juvenile fiction; Rain and rainfall -- Juvenile fiction; Umbrellas -- Juvenile fiction; Animals -- Fiction; Hedgehogs -- Fiction; Rain and rainfall -- Fiction; Umbrellas -- Fiction; Animals -- Fiction; Board books for children, English; Hedgehogs -- Fiction; Rain -- Fiction; Umbrellas and parasols -- Fiction